Fördernde Wirkung extracurricularer Angebote an Ganztagsgrundschulen Eine quasi-experimentelle Studie im Bereich Naturwissenschaften - Schröder, Julia (Universitätsverlag Göttingen, 2021)
The expansion of all-day schools should lead, among other things, to a changed teaching and learning culture that promotes motivational-affective competencies in students. But even after 20 years, all-day elementary schools do not seem to fulfill this. Scientific quality criteria are too rarely implemented in elementary schools. The aim of this dissertation was to investigate the effect of an (interlocked) extracurricular science program on elementary school students regarding their motivational-affective characteristics. For this purpose, an (interlocked) offer was implemented in the intervention study, whereby this was linked to physical education in half of the schools. The analysis of the questionnaires of 236 pupils showed that participation in a science offer can be profitable, but that the interlocking is not as highly effective as expected. The study suggests changing the intra-school structure and revising the understanding of interlocking.